Procedural recommendations of cardiac PET/CT imaging: standardization in inflammatory-, infective-, infiltrative-, and innervation- (4Is) related cardiovascular diseases: a joint collaboration of the EACVI and the EANM: summary. (27th November 2020) - Slart, Riemer H J A; Glaudemans, Andor W J M; Gheysens, Olivier; Lubberink, Mark; Kero, Tanja; Dweck, Marc R; Habib, Gilbert; Gaemperli, Oliver; Saraste, Antti; Gimelli, Alessia; Georgoulias, Panagiotis; Verberne, Hein J; et al.
Abstract: With this summarized document we share the standard for positron emission tomography (PET)/(diagnostic)computed tomography (CT) imaging procedures in cardiovascular diseases that are inflammatory, infective, infiltrative, or associated with dysfunctional innervation (4Is) as recently published in the European Journal of Nuclear Medicine and Molecular Imaging. This standard should be applied in clinical practice and integrated in clinical (multicentre) trials for optimal standardization of the procedurals and interpretations. A major focus is put on procedures using [ 18 F]-2-fluoro-2-deoxyglucose ([ 18 F]FDG), but 4Is PET radiopharmaceuticals beyond [ 18 F]FDG are also described in this summarized document. Whilst these novel tracers are currently mainly applied in early clinical trials, some multicentre trials are underway and we foresee in the near future their use in clinical care and inclusion in the clinical guidelines. Diagnosis and management of 4Is related cardiovascular diseases are generally complex and often require a multidisciplinary approach by a team of experts. The new standards described herein should be applied when using PET/CT and PET/magnetic resonance, within a multimodality imaging framework both in clinical practice and in clinical trials for 4Is cardiovascular indications.